STATISTICAL OPTIMISATION OF THE CRUDE MEDIA AND COMPONENTS FOR ENHANCED PRODUCTION OF BACTERIOCIN FROM BACILLUS SPECIES BY PLACKETT- BURMAN DESIGN. - SUPRIYA KAMATHE; PROF. SAVANTA V. RAUT (International Journal of Pharma and Bio Sciences, 2014)
A Bacillus strain producing a bacteriocin-like substance was isolated from mangrove soil & identified by biochemical profiling and 16S rRNA sequencing. Phylogenetic analysis indicated that the strain has high sequence similarity with Bacillus licheniformis. The culture supernatant of B. licheniformis exhibited bacteriocin-like activity against Gram-positive and Gram negative bacteria and fungi. Enhancement of bacteriocin activity was tested using cheap crude sources like molasses, corn steep liquor and cheese whey. Corn steep liquor and cheese whey is rich nitrogen sources rather than carbon sources. Selection of the crude media sources was done by Students t-test where corn-steep liquor for Bacillus licheniformis was found to be significant. Optimization using Plackett-Burman design showed Sodium chloride, potassium nitrate, sugar,as the most important variables for bacterocin production in the first step of media. The stability study shows bacteriocin produced by Bacillus licheniformis was stable over a wide pH (3-11) and temperature [4-37 0 C]. A low-molecular-weight bacteriocin-like protein from B. licheniformis exhibited a wide spectrum of antimicrobial activity. A 2-fold increase in the production of bacteriocin was achieved using the culture medium optimized through Plackett-Burman design.